PENENTU SIKAP DAN PENGARUHNYA TERHADAP NIAT PEMBELIAN PADA SITUS WEB PENJUALAN KEMBALI - Yowanda, Dinda; Kurniawati, Kurniawati (Universitas Prof. Dr. Hazairin SH, 2022)
The research was conducted to examine the effect of six consumption values (functional benefits, emotional benefits, social benefits, epistemic benefits, economic benefits and trust) on attitudes towards purchase intention. In addition, the authors also use Thaler's utility theory to determine the indirect effect of utility and transaction utility on purchase intentions. The author conducted a survey of the general public whose respondents had online shopping experience on online resale platforms such as Shopee, Tokopedia and Bukalapak with a total of 220 samples, using the Google form and partial least squares structural equation modeling (PLS-SEM) to test the relationship hypothesis in the model filed. Findings, the results of the study indicate that attitudes mostly function to create positive attitudes there is purchase intention, followed by trust, social, emotional and functional benefits. however, the epistemic and economic benefits of purchasing experience with an online sales website failed to influence positive attitudes in customers